2019
DOI: 10.1136/bmjopen-2018-027158
|View full text |Cite
|
Sign up to set email alerts
|

Association between continuity of provider-adjusted regularity of general practitioner contact and unplanned diabetes-related hospitalisation: a data linkage study in New South Wales, Australia, using the 45 and Up Study cohort

Abstract: ObjectiveTo assess the association between continuity of provider-adjusted regularity of general practitioner (GP) contact and unplanned diabetes-related hospitalisation or emergency department (ED) presentation.DesignCross-sectional study.SettingIndividual-level linked self-report and administrative health service data from New South Wales, Australia.Participants27 409 survey respondents aged ≥45 years with a prior history of diabetes and at least three GP contacts between 1 July 2009 and 30 June 2015.Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
2
21
1
Order By: Relevance
“…Unlike other studies evaluating rates or cost of hospitalisation [ 12 , 16 , 20 , 44 , 47 ] we did not find a strong inverse association across increasing regularity levels. This may have been due to the outcomes we evaluated having a different relationship with regularity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other studies evaluating rates or cost of hospitalisation [ 12 , 16 , 20 , 44 , 47 ] we did not find a strong inverse association across increasing regularity levels. This may have been due to the outcomes we evaluated having a different relationship with regularity.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the issues in assessing regularity is in disentangling its effects from those of continuity of provider and frequency of care. Again, among a cohort of people with diabetes, higher regularity (adjusted for continuity of provider and frequency of GP attendance) showed an association with lower costs for unplanned hospitalisation, suggesting that regularity is a discrete facet of continuity of care [ 20 ]. Previous analyses have suggested that regular primary care provision may also be associated with fewer readmissions [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As continuity of care is seldom applied in EDs when compared with office-hours primary care [4][5][6], organising distribution of work differently between these two health care providers might enhance this continuity [4,16]. It is not only the continuity of care by certain individual care providers which matters but also provider-adjusted regularity of the contacts [17]. To support this view, a large global study (34 countries during the years 2011 to 2013) found that adequate access to primary care decreased ED visits [18].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Various aspects of primary health care utilisation can be measured using a variety of tools such as frequency of GP contacts, continuity of provider and regularity of GP contacts. [8][9][10][11][12] Regularity of GP contacts captures the dispersion of GP contacts, i.e. the extent of the variation in time intervals between contacts with a GP.…”
Section: Introductionmentioning
confidence: 99%
“…Regularity has therefore been suggested as a suitable target for health policy interventions aiming at reducing avoidable hospitalisations and controlling healthcare resource use. 12,16 Although literature highlights the benefit of regular contacts with GPs among certain chronic conditions, limited evidence exists on whether the effect of regularity on hospitalisation may be modified by multimorbidity. Given the high burden of multimorbidity, a better understanding of how multimorbidity may modify the relationship between regularity of GP contact and the risk of hospitalisation would inform whether current primary healthcare delivery models need to be reorganised for people with certain levels of multimorbidity.…”
Section: Introductionmentioning
confidence: 99%